Dental Characteristics of Late Pleistocene Equus Lambei from the Bluefish Caves, Yukon Territory, and their Comparison with Eurasian Horses - Burke, Ariane; Cinq-Mars, Jacques (Géographie physique et Quaternaire, 1996)
ABSTRACTBluefish Caves I, II and III of northern Yukon, have yielded the earliest in situ evidence of human occupation of Eastern Beringia, associated with one of the largest and most diverse Late Pleistocene faunas recovered in the region. This paper presents data derived from the study of a large sample of horse teeth recovered from the three caves. This research contributes to our knowledge of the Late Pleistocene Beringian equid, Equus lambei. A comparison of the dentition of E. lambei with that of some contemporary European horses, indicates they have similar size cheekteeth. The hypothesis of a Late Pleistocene trend of size reduction in equids is considered in the light of this comparison.